Clinical Features of Optic Disc Drusen in an Ophthalmic Genetics Cohort. (6th October 2020) - Serpen, Jasmine Y.; Prasov, Lev; Zein, Wadih M.; Cukras, Catherine A.; Cunningham, Denise; Murphy, Elizabeth C.; Turriff, Amy; Brooks, Brian P.; Huryn, Laryssa A.
Abstract : Background/Aims . Optic disc drusen (ODD) are calcified deposits of proteinaceous material in the optic disc, and their burden in ocular conditions is unknown. As ODD can be associated with visual field defects further compromising already degenerating visual function in patients with retinal degenerations, it is important to further our knowledge of ODD in inherited eye disease. The present study aims to evaluate prevalence, demographic features, and optic disc parameters of eyes with superficial ODD in inherited eye conditions. Materials and Methods . Electronic medical records of patients evaluated in the Ophthalmic Genetics clinic at the National Eye Institute (NEI) between 2008 and 2018 were searched for a superficial ODD diagnosis. Color fundus and autofluorescence images were reviewed to confirm ODD, supplemented with optical coherence tomography (OCT) in uncertain cases when available. Demographic information, examination, and genetic testing were reviewed. Disc areas and disc-to-macula distance to disc diameter ratios (DM : DD) were calculated. Results . Fifty six of 6207 patients had photographically confirmed ODD (0.9%). Drusen were predominantly bilateral (66%), with a female (62%) and Caucasian (73%) predilection. ODD prevalence in our cohort of patients with inherited retinal degenerations was 2.5%, and ODD were more prevalent in the rod-cone dystrophy subgroup at 2.95% (OR = 3.3 [2.1–5.3], P < 0.001 ) compared to the ophthalmic genetics cohort. Usher patients were more likely to have ODD (10/132, 7.6%, OR = 9.0 [4.3–17.7], P < 0.001 ) and had significantly smaller discs compared to the rest of our ODD cohort (disc area: P = 0.001, DM : DD: P = 0.03 ). Discussion . While an association between ODD and retinitis pigmentosa has been reported, this study surveys a large cohort of patients with inherited eye conditions and finds the prevalence of superficial ODD is lower than that in the literature. Some subpopulations, such as rod-cone dystrophy and Usher syndrome, had a higher prevalence than the cohort as a whole.